BLOCKCHAIN FOR PATIENT DATA SECURITY: POTENTIAL AND CHALLENGES - Loso Judijanto; Arnes Yuli Vandika; Lola Yustrisia (CV. ADIBA AISHA AMIRA, 2025)
The use of blockchain applications in the health sector, in patient data security, promises significant progress in the management and protection of medical information. Database decentralization, which is at the heart of blockchain technology, presents itself as an innovative solution in reducing the risk of cyber attacks and system failures simultaneously, by dividing information into scattered networks. It increases patient information resilience to data loss and identity theft. Another advantage of blockchain is greater transparency and auditability. Any transactions or changes recorded cannot be changed again, ensuring consistent data integrity. This is crucial in a healthcare environment, where errors in patient information can have serious implications for patient care and health outcomes. In addition, the blockchain system allows the use of strong encryption and layered access controls, making patient data much safer from unauthorized access. However, despite the many advantages it offers, there are challenges to overcome in order for this technology to be implemented effectively. Challenges such as system scalability, complex regulatory compliance, and difficulty integrating with existing health information technology systems are major obstacles to blockchain implementation. Concerns about scalability emphasize increased processing time and operating costs as transaction volumes grow. Regulatory compliance often requires extra care and adaptation to strict local regulations relating to personal data and privacy.